A Transgender Teacher’s Pre-Service Experience - Karen Terry; Gayle Ramirez; Andrea Jane Ramirez; Barbara Radcliffe; Deborah Paine; JT Cox (Brock Education: a Journal of Educational Research and Practice)
This qualitative, single-subject case study examines a transgender pre-service teacher’s experiences completing an educator preparation program (EPP) in a predominantly rural region in the southeast United States. The purpose of this case study is to describe and understand a transgender pre-service teacher’s experiences in finding and completing the field experience requirements across multiple school districts. Stories of the participant’s experiences, university faculty members’ accounts, and communication documents inform the research. Results demonstrate obstacles the preservice teacher faced during their field placement and hindrances to securing employment post-graduation. Implications for further research are discussed.